ANALISIS STRUKTUR BIAYA, TITIK IMPAS, DAN PENDAPATAN USAHATANI PADI PADA KELOMPOK TANI TUNAS KARYA MANDIRI KELURAHAN BANJARSARI KECAMATAN METRO UTARA KOTA METRO - Herisonti, Dina Afrida; Endaryanto, Teguh; Nugraha, Adia (Lampung University, 2022)
This study aims were to analyze the cost structure; revenue, production, and price break even point; and the level of income of rice farming. This research was conducted in Banjarsari Village, North Metro Sub District, Metro District. This research used survey method. The data were taken in April-May 2021. The sample were all members of the Tunas Karya Mandiri Farmer Group amounting to thirty-two farmers. Methods of data analysis are descriptive quantitative. The results showed that the cost structure of the largest variable cost component lies in the cost of labor outside the family by 44.21% and the largest fixed cost component in the cost of land rent by 30.25% of the total cost. The value of the BEP of rice farming revenue was IDR6,071,490.06/ha, the BEP of rice production was 1,607.03kg/ha and the BEP of GKP (Dry Harvested Grain) was IDR 2,061.73/kg. The BEP value is smaller than the actual value received, namely the revenue of IDR18,951,023.90/ha; rice production was 5,018.52 kg/ha, and the selling price of GKP was set at IDR3,778.85/kg. The total income obtained was IDR7,707,474.91/ha with an R/C of 1.69 so that rice farming was profitable and feasible to continue.Key words: Rice, cost structure, break even point, income